Need help from an expert?
The world’s top online tutoring provider trusted by students, parents, and schools globally.
The integral of x*e^x is (x-1)*e^x + C, where C is the constant of integration.
To find the integral of x*e^x, we can use integration by parts. Let u = x and dv/dx = e^x. Then du/dx = 1 and v = e^x. Using the formula for integration by parts, we have:
∫x*e^x dx = x*e^x - ∫e^x dx
The integral of e^x is simply e^x, so we have:
∫x*e^x dx = x*e^x - e^x + C
where C is the constant of integration. We can simplify this expression by factoring out e^x:
∫x*e^x dx = (x-1)*e^x + C
This is our final answer. We can check it by differentiating to see if we get back to the original function:
d/dx [(x-1)*e^x] = e^x + x*e^x - e^x = x*e^x
So the derivative of (x-1)*e^x is indeed x*e^x, which confirms that our answer is correct.
Study and Practice for Free
Trusted by 100,000+ Students Worldwide
Achieve Top Grades in your Exams with our Free Resources.
Practice Questions, Study Notes, and Past Exam Papers for all Subjects!
The world’s top online tutoring provider trusted by students, parents, and schools globally.